Development of Sound Experimentation Tool using Android-Based Sound Analysis Oscilloscope Software - Syaifuddin Syaifuddin; Putut Marwoto; Retno Sri Iswari; Edy Cahyono; Sarwi Sarwi (Postgraduate, University of Mataram, 2022)
Experimental activities are part of physics learning process with the aim of gaining knowledge and having good understanding of physics concepts. Sound and organ pipes are the main subjects discussed in physics and engineering lessons. These materials contain facts accompanied by actualization in everyday life in social life. However, the fact in high school (SMA) physics learning is that experimental activities in supporting students’ learning and understanding have not been widely carried out. This is due to the lack of practical support tools. The purposes of this research are to design a sound experimentation tool design of an open and closed organ pipes and to determine the value of the speed of sound which propagates through air medium using a data acquisition technique assisted by sound analysis oscilloscope software. This type of research is a Research and Development research with five stages referring to the ADDIE model. The first stage was analysis, that was done by conducting a study of the problems of physics learning at senior high school level, especially in sound chapter. The second stage was design, namely designing experimentation tools. The third stage was development, that was done by providing materials that were used in the experiment. The fourth stage was implementation, that was testing the tool which had been made combined with sound analysis oscilloscope software, and the fifth was conducting an evaluation and feasibility test based on the validity of the experimental data. The data analysis technique used average and linear regression by utilizing the results of data from frequency analysis using sound analysis oscilloscope software. The results showed that the experimentation tool in this study was able to be used as learning media for the sound and open and closed organ pipes materials. The experimental results obtained that the speed of the sound waves propagation in air for an open organ pipe was v = 332.19 m/s with an accuracy rate of 97.70%. While the value of the speed of the sound waves in air for a closed organ pipe was v = 334.69 m/s with an accuracy rate of 98.44%.